An Empirical Analysis of Islamic Banking (IBs) Contribution to Indonesia’s Inclusive Growth - Ibrahim, Muhammad Yusuf; Indra, Indra (International Journal of Islamic Economics and Finance (IJIEF), 2021)
The research is aim to attest and assess empirically the contribution of Islamic banking (IBs) on the inclusive growth in Indonesia. By taking a trial-stage method i.e. descriptive analysis to elaborate a statistical data, autoregressive distributed lag (ARDL) model to assess empirically the contribution in a long-term, and error correction model (ECM) to assess the contribution in a short-term empirically. The findings are, total deposits and total financing only contribute positively significant into GDP and gini ratio in a long-term, that similiar with the previous study. Then, a total financing contribute negatively to all indicators of inclusive growth in a long-term, but, its only significance on GDP and gini ratio. But, it was contribute significantly to all indicators in a short-term. So. The findings was only evidence the significance contribution of IBs on inclusive growth in a short-term. Based on it, a long-term contribution of IBs still cathegorized as the area that requires an extentions in order to accomplish it. Â